Luxury Community-Based Tourism: The Enhancement of Local Experiences in Phuket - Chumnanchar, Benjamaporn; Wongsaroj, Sirinpa (วารสารเพื่อการพัฒนาการท่องเที่ยวสู่ความยั่งยืน, 2024)
Community-based tourism has benefited from a direct economic impact on families, socioeconomic enhancements, and sustainable lifestyle diversification in 7 local communities in Phuket. This academic article aims to present and analyze major local communities in Phuket. This article provides a detailed analysis of Luxury Community-Based Tourism, Tourist Luxury Experiences and their enhancement to become luxury community-based tourism in Phuket. Community-based tourism in Phuket must empower its concepts to reach new targets of tourists, especially to engage luxury tourists. By focusing on locally and independently owned participation in local communities, 7 community-based tourism sites in Phuket have enhanced their standards to provide exclusivity, authenticity, and enjoyment to create cultural and spiritual experiences for new targets of tourists. At the same time, these communities can create products and services that are environmentally conscious, sustainable, and socially responsible in the area. However, community-based tourism in Phuket should consider more closely customized and individualized based on the needs and motivations of tourists. High-priced tourist products and high-quality services should be provided to encourage luxury tourism establishments in the area.